Enhancing functional safety in FPGA-based motor drives - Benjamin Peter Jeppesen (The Journal of Engineering, 2019)
Motor control applications using small fast-spinning motors, and the advent of SiC and GaN switching transistors, are driving a need for compact drives with high-frequency control loop updates. FPGAs provide the necessary speed and flexibility for such control. Drives must also adhere to functional safety standards. This paper demonstrates how the functional safety of an FPGA-controlled drive can be analysed using an FMEDA and enhanced with diagnostic methods to achieve ISO 26262 ASIL B or IEC 61508 SIL 2.